Serum preptin and amylin levels in acne vulgaris patients - Gürok, Neşe Göçer; Kökçam, İbrahim; Cıcek, Demet; Aydin, Suleyman; Aygun, A. Denizmen (My University, 2019)
Acne vulgaris is a common disease with multi-factorial etiology that occupies the pilosebaceous unit. Several recent studies demonstrated that insulin and insulin resistance can play a role in acne pathogenesis. In the present study, the roles of preptin and amylin, which are directly associated with insulin secretion and released from pancreas beta cells, in acne vulgaris pathogenesis were investigated. The study was conducted with 40 cases with acne vulgaris and the control group that included 40 healthy subjects with similar body mass index. Serum preptin and amylin levels and fasting blood glucose, triglyceride, total cholesterol, LDL, VLDL, HDL, C-peptide, insulin and HbA1c levels were examined in the study group. HOMA-IR values were calculated. Although patient group serum preptin and amylin levels were higher when compared to the control group, however the difference was not statistically significant (p> 0.05). It was determined that there was a positive correlation between severity of the disease and amylin levels. In the patient group, it was found that the glucose level was significantly higher when compared to the control group (p <0.001). Serum insulin and C-peptide levels and HOMA-IR index were higher in the patient group when compared to the control group, however the difference was not statistically significant (p> 0.05). It is considered that increased preptin and amylin levels in acne vulgaris patients may be associated with the etiopathogenesis of the disease. We also considered that decreasing the elevated levels of these two peptides to normal levels may be helpful for the treatment of the disease.
Keywords: Dermatoloji; Endokrinoloji ve Metabolizma